Genetic control of thermoinhibition tolerance in lettuce seeds - Oliveira, Daniele de Fátima; Cavasin, Pedro Yuri; Silva, Sylmara; Oliveira, Natália Souza; Oliveira, Cleiton Lourenço de; Gomes, Luiz Antonio Augusto (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to assess the genetic control of tolerance to thermoinhibition in lettuce (Lactuca sativa) seeds. Seeds of the F1, F2, and F2:3 generations derived from the cross between cultivars Everglades (tolerant to thermoinhibition) and Verônica (sensitive to thermoinhibition) were used, besides seeds from the parents. Seed germination tests were conducted in a completely randomized design, with four replicates of each parent, eight of F1, and four of each of the 26 F2:3 progenies. The mean of the F2 population was considered as the mean of the sample of the 26 progenies. The genetic control of thermoinhibition tolerance in lettuce seeds is attributed to one or a few genes. The additive effects are more expressive than the nonadditive ones, and narrow-sense heritability is relatively high, allowing the prediction of success in selection.
Keywords: Lactuca sativa; genetic variability; heritability; seed germination